Learning of Badminton for Class V Elementary School - Badruddin (Marga: Journal Of Innovation and Creatifity, 2023)
The general aim of this research is to improve student outcomes through the application of badminton learning using a Scientific Approach. Apart from that, this research was conducted to obtain in-depth information about the application of badminton learning. The design of this research is Action Research. The subjects in this research were 24 students from class five at SD Negeri 2 Nisam Antara. This research was conducted in two meetings of two cycles. The first cycle shows that through action students can motivate themselves. From this cycle the result is 79% and that means it is complete. In the second cycle, as a reflection of the first cycle, it also shows that actions motivate students. The result of the second cycle is 92% and that means it is complete. Based on the results of this research, it can be concluded that: (1) Badminton learning using the Scientific Approach improves student learning outcomes, (2) Badminton learning using the Scientific Approach motivates students and makes students actively participate in the learning process.